Engineering Person-Specific Behavioral Interventions to Promote Physical Activity - Conroy, David E; Lagoa, Constantino M; Hekler, Eric; Rivera, Daniel E (Exercise and sport sciences reviews, 2020)
Physical activity is dynamic, complex, and often regulated idiosyncratically. In this article, we review how techniques used in control systems engineering are being applied to refine physical activity theory and interventions. We hypothesize that person-specific adaptive behavioral interventions grounded in system identification and model predictive control will lead to greater physical activity than more generic, conventional intervention approaches.